Liquidity risk and bank performance during financial crises - Chen, Wei-Da; Chen, Yehning; Huang, Shu-Chun (Journal of Financial Stability, 2021)
Using U.S. bank data from 1996 to 2013, this paper studies how liquidity risk affects bank performance in financial crises. It finds that during the subprime crisis of 2007–09, liquidity risk reduced a bank’s survival probability, ROA, and net interest margin, and increased its loan-loss-provision expenses. This adverse effect was more severe for banks with lower capital ratios and higher credit risk. In contrast, there is no strong evidence that liquidity risk hurts bank performance in market crises. The results in this paper imply that liquidity risk is not merely a symptom of banks’ insolvency problems; it has an independent effect on bank performance in banking crises.